The effects of spiritual-psychological synthesis on anxiety, depression, and mental health of Vietnamese refugees - Giong, Marie Thecla Tran Thi (Animo Repository, 1993)
The techniques of spiritual-psychological synthesis (SPS), which the researcher formulated based on the idea of combining psychology and spirituality, consists of prayer, inner conversion and group support which were used to help the Vietnamese Catholic refugees in Bataan to reduce their depression and state and trait anxiety and improve their mental health. This research made use of pretest/posttest, posttest/delayed posttest control group design. Beck Depression Inventory (BDI), State-Trait Anxiety Inventory (STAI-S and STAI-T), and Mental Health Pictograph Questionnaire (MHPQ) were used as instruments.The subjects were 18 males and 20 females, with age ranging from 18-46 (M=26.82). All voluntered to participate. They were randomly assigned, 26 in the experimental and 12 in the control group. Two from the experimental and one from the control group dropped out. Only 21 of the experimental and 9 of the control group subjects were present at the delayed posttest.The treatment lasted for 7 consecutive days with 4 1/2 hours sessions daily.The results of the t-test show that in the experimental group, the reduction of depression and anxiety is significant, and the improvement of mental health is significant in 5 or 7 areas (mood states, thought process, activity, organization/control, interpersonal behavior). The ANCOVA results between the experimental and control groups from pretest to posttest show a significantly greater reduction in the level of depression and anxiety of the experimental group. Two areas of mental health (thought process and organization/control) show a significantly greater improvement for the experimental group.The ANCOVA results between the experimental and control groups from posttest to delayed posttest show that there is no significant difference in change.The SPS intervention is an effective tool for the reduction of depression and anxiety and the improvement of mental health.